When Reviews Matter More: Exploring the Influence of Online Customer Reviews and Brand Awareness on Purchase Intention - Dwi Prasetyo, Benny; Vania, Amelindha (ILTIZAM Journal of Shariah Economics Research, 2025)
Online food delivery is the main choice of Indonesians, along with lifestyle changes that prioritize comfort, convenience, and time efficiency. This study aims to analyze the effect of online customer reviews and brand awareness on consumer purchase intention, especially on Gacoan Noodle products sold through the ShopeeFood application. Data was mainly collected by using a quantitative approach, data was distributed to consumers who have bought Mie Gacoan product form questionnaire. The analysis method used is Structural Equation Modeling (SEM) with the help of SmartPLS software. The results showed that online customer reviews have a significant influence on the purchase intention of Gacoan Noodle consumers on ShopeeFood in Malang City. Conversely, although brand awareness plays an important role in brand recognition, its effect on purchase intention is not partially significant. However, simultaneously, these two independent variables can explain most of the variation in the purchase intention of Gacoan Noodle consumers on the ShopeeFood application in Malang City.